GABAergic and glycinergic inhibitory synaptic transmission in the ventral cochlear nucleus studied in VGAT channelrhodopsin-2 mice - Xie, Ruili; Manis, Paul B. (Frontiers in Neural Circuits, 2014)
Both glycine and GABA mediate inhibitory synaptic transmission in the ventral cochlear nucleus (VCN). In mice, the time course of glycinergic inhibition is slow in bushy cells and fast in multipolar (stellate) cells, and is proposed to contribute to the processing of temporal cues in both cell types. Much less is known about GABAergic synaptic transmission in this circuit. Electrical stimulation of the auditory nerve or the tuberculoventral pathway evokes little GABAergic synaptic current in brain slice preparations, and spontaneous GABAergic miniature synaptic currents occur infrequently. To investigate synaptic currents carried by GABA receptors in bushy and multipolar cells, we used transgenic mice in which channelrhodopsin-2 and EYFP is driven by the vesicular GABA transporter (VGAT-ChR2-EYFP) and is expressed in both GABAergic and glycinergic neurons. Light stimulation evoked action potentials in EYFP-expressing presynaptic cells, and evoked inhibitory postsynaptic potentials (IPSPs) in non-expressing bushy and planar multipolar cells. Less than 10% of the IPSP amplitude in bushy cells arose from GABAergic synapses, whereas 40% of the IPSP in multipolar neurons was GABAergic. In voltage clamp, glycinergic IPSCs were significantly slower in bushy neurons than in multipolar neurons, whereas there was little difference in the kinetics of the GABAergic IPSCs between two cell types. During prolonged stimulation, the ratio of steady state vs. peak IPSC amplitude was significantly lower for glycinergic IPSCs. Surprisingly, the reversal potentials of GABAergic IPSCs were negative to those of glycinergic IPSCs in both bushy and multipolar neurons. In the absence of receptor blockers, repetitive light stimulation was only able to effectively evoke IPSCs up to 20 Hz in both bushy and multipolar neurons. We conclude that local GABAergic release within the VCN can differentially influence bushy and multipolar cells.